Preferences of Students of Free Courses on the Modalities of Fitness or Wellness According to Sex - Anchía-Umaña, Irina; Elizondo-Monge, Ashley; Monge-Poltronieri, Steve; Revuelta-Sánchez, Inés; Sánchez-Ureña, Braulio; Gutiérrez-Vargas, Juan Carlos (Revista Electrónica Educare, 2019)
The object of the present study was to determine, according to sex, the preference in courses registered by students, regarding the modalities of Fitness or Wellness in the Free-courses Programs of the Escuela Ciencias del Movimiento Humano y Calidad de Vida (CIEMHCAVI) of the Universidad Nacional in Costa Rica. Procedure: The research was conducted under a retrospective approach, with data obtained from records from the years 2012 to 2016. Participants: a sample of 2112 students aged 17 to 62 years and 28.3 ± 7.8 years, (1181 men and 931 women), enrolled in one or more of the Free-courses Programs taught between 2012 and 2016 at CIEMHCAVI/UNA. The variables studied were gender, age, course/s registered, and approval or disapproval. Results: There are statistically significant differences (χ 2 = 141.916, p = <.001) in the registration preferences of the modality (Fitness or Wellness) according to sex, but no differences found between quartiles of ages (X2(3) = 2,939., p=<.40) or gender classification in the percentages of approval or failure of the courses (χ 2 = .064, p = <.800).